Secondary Rhinoplasty for Unilateral Cleft Nasal Deformity. Issue 1 (July 2021) - Rohrich, Rod J.; Benkler, Michal; Avashia, Yash J.; Savetsky, Ira L.
Abstract : Background: Secondary cleft rhinoplasty presents some of the most challenging cases of both cosmetic and functional nasal deformities. Understanding the anatomy and growth abnormality seen with the cleft nasal deformity helps to tailor surgical management. This article seeks to expand on the application of current concepts in secondary rhinoplasty for unilateral cleft lip nasal deformity. Methods: The authors review nasal analysis in the cleft rhinoplasty patient and provide the surgical management for each aspect in the secondary cleft rhinoplasty. Results: The secondary rhinoplasty was divided into seven areas: piriform hypoplasia, septal reconstruction, dorsal reshaping, tip reshaping, tip projection, alar reshaping, and alar repositioning. Surgical management for each is provided. Conclusion: Secondary cleft rhinoplasty requires an understanding of the structural dysmorphology, and the use of cosmetic, functional, and secondary rhinoplasty techniques for its successful management.